2018
DOI: 10.1167/iovs.18-23880
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light of Different Spectral Composition on Refractive Development and Retinal Dopamine in Chicks

Abstract: Red, blue, and UV lighting all stimulated the release of retinal DA, but there were wavelength-dependent differences in DA release and metabolism. Less deprivation myopia developed in UV and blue lighting, compared to white and red light. The application of these findings to humans is limited by the fact that, different from chicks, humans have very low sensitivity in the near-UV region of the spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 54 publications
1
68
1
Order By: Relevance
“…The anterior segment of the eye was discarded. Vitreous and retina were prepared as described before, 27 instantly frozen in liquid nitrogen, and stored at À808C. Catecholamines were quantified with HPLC-electrochemical detection (Ultimate 3000 LC with electrochemical detection ECD3000RS; Thermo Fisher Scientific, Waltham, MA, USA) as previously described.…”
Section: Inhibition Of Myopia With Artificial Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…The anterior segment of the eye was discarded. Vitreous and retina were prepared as described before, 27 instantly frozen in liquid nitrogen, and stored at À808C. Catecholamines were quantified with HPLC-electrochemical detection (Ultimate 3000 LC with electrochemical detection ECD3000RS; Thermo Fisher Scientific, Waltham, MA, USA) as previously described.…”
Section: Inhibition Of Myopia With Artificial Stimulimentioning
confidence: 99%
“…Catecholamines were quantified with HPLC-electrochemical detection (Ultimate 3000 LC with electrochemical detection ECD3000RS; Thermo Fisher Scientific, Waltham, MA, USA) as previously described. 27 Vitreous was mixed with 750 lL mobile phase (Thermo Fisher Scientific) and homogenized with a tissue lyser (TissuesLyser LT; Qiagen, Hilden, Germany) at 50 Hz for 4 minutes, while the retina was disrupted with 500 lL mobile phase and 25 lL of the homogenate was saved for later protein measurements. Both the vitreous and retina homogenates were centrifuged at 14,000g for 10 minutes, the supernatant filtered through a 0.2-lm nylon membrane sample filter (Thermo Scientific, Rockwood, IL, USA), and 25 lL was directly injected into the HPLC system.…”
Section: Inhibition Of Myopia With Artificial Stimulimentioning
confidence: 99%
“…All homogenized samples were centrifuged at 4 ° C for 10 min at 14,000 g. The supernatant was filtered through a 0.2-µm nylon membrane filter (Thermo Scientific, Rockwood, MI, USA), and 25 µL was directly injected into the HPLC system. Samples were analyzed for catecholamine and indolamine content by HPLC (Ultimate 3000 LC with electrochemical detection ECD3000RS, Thermo Fischer Scientific) with coulometric detection as previously described [39]. In brief, a hypersil C18 column was used (150 × 3 mm, 3 µm) together with a test mobile phase (Thermo Fischer Scientific) containing 10% acetonitrile and 1% phosphate buffer.…”
Section: Sample Preparation and Measurement Of Biogenic Amines By Hplmentioning
confidence: 99%
“…Recently, it has been demonstrated that also vitreal HVA content DOI: 10.1159/000502529 is a good measure of dopamine turnover, since HVA content in the vitreous was significantly correlated with the amount of vitreal DOPAC [39].…”
Section: Sample Preparation and Measurement Of Biogenic Amines By Hplmentioning
confidence: 99%
“…blue light [34]. Besides the anti-myopic effect of blue light attributed to the myopic defocus it causes on the retina (discussed above) [20], it has a further protective effect mediated in part by dopamine through pre-and postsynaptic connections of ipRGCs to dopaminerg amacrin cells [35]. Dopamine has been long acknowledged as a retinal neurotransmitter acting against myopia development, and it has also been evidenced that blue light stimulates a larger amount of dopamine release than other wavelengths do [35].…”
Section: Discussionmentioning
confidence: 99%